The evolutionary system of the biosphere: a dialectical approach - Alexander Protasov (Geo&Bio, 2023)
The dialectics of evolution is that the development of various systems, complication is determined by several principles, which themselves are similar to emergent systems based on opposite but dialectically complementary categories and concepts. A new concept of evolution of the biosphere as an integral system of its successive states united by development trends is proposed. The structure of the biosphere is considered as a fractal system with the ecosystem as its elementary unit. The next fractal levels are biogeomes and biospheromerons. The fractal structure corresponds to the principle of emergence. The proposed concept of biosphere evolution is based on general naturalistic principles and categories of dialectics, such as states and interstates, continuity and discreteness, reproducibility and uniqueness, the hypothesis of information channels or trends, the concept of biosphere organisation in a specific evolutionary space-time. In general, the evolutionary history of the biosphere is a metameric picture of changing states and interstates. A complex system of continuums is the most important feature of the biosphere’s organisation in space-time. Continuity of the first kind can be observed when there is a continuum of indistinguishability within a continuing state: during a long geological time, there were no cardinal changes in the structure of biosphere elements and connections between them. At the same time, the development of an integral biosphere system occurs in a continuum of the second kind: given the continuity of life, the differences between the early and subsequent states are very significant and obvious in the biosphere. Moreover, these differences are associated with complication, development, which is, in fact, evolution. The states of the biosphere in certain periods are connected by trends, which form an evolutionary system. Continuing states, when the system remains self-identical for a long period, are replaced by new states through interstates. Thus, a specific type of continuum, the metameric continuum, is formed. The taxonomic, ecomorphic, symbiotic, and ecosystem trends are identified and considered as the main ones in the evolution of the biosphere. The Vernadsky–Margalef hypothesis of the origin of life and biosphere in the form of protoecosystems is considered and supported.